2018
DOI: 10.1080/21645515.2018.1515448
|View full text |Cite
|
Sign up to set email alerts
|

Is immunisation education in midwifery degrees adequate?

Abstract: Maternal and childhood vaccination decisions begin during pregnancy, and midwives are an important information resource. Their role is set to increase with the expansion of maternal immunisations into new jurisdictions, and new maternal vaccines in development. Meanwhile, other health providers are orienting parents towards vaccine acceptance, using strategies at odds with midwifery norms around information provision and maternal autonomy. To better understand and address the implications of these developments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…This represents an improvement from earlier research conducted in Australia, 20 which found 40% of midwives were unsure if there was an association between the MMR vaccine and autism. While this theory has been thoroughly discredited 21 and fewer midwives appear to be vaccine-hesitant as a result, our study shows that some midwives may still be uncertain. Similarly, one-third of midwives in our study either believed that vaccines caused allergies, or were not sufficiently confident that vaccines did not cause allergies.…”
Section: Discussionmentioning
confidence: 65%
“…This represents an improvement from earlier research conducted in Australia, 20 which found 40% of midwives were unsure if there was an association between the MMR vaccine and autism. While this theory has been thoroughly discredited 21 and fewer midwives appear to be vaccine-hesitant as a result, our study shows that some midwives may still be uncertain. Similarly, one-third of midwives in our study either believed that vaccines caused allergies, or were not sufficiently confident that vaccines did not cause allergies.…”
Section: Discussionmentioning
confidence: 65%
“…Midwives see lack of knowledge as a barrier to practise, and it has been demonstrated that midwives practise benefits significantly from immunisation education. There is little evidence to suggest that midwives received or benefitted from, any immunological or vaccination related education provided in Bachelor of Midwifery courses [43]. Additionally, midwives who had received training via the Understanding Immunisation courses stated that they benefitted from it in terms of both education, confidence and vaccine provision.…”
Section: Resultsmentioning
confidence: 99%
“…Midwives who were interviewed identified lack of education in undergraduate courses as a significant barrierto practise. Additionally, survey data revealed that whilst 75.8% agreed it was their role to offer the influenza immunisation, whilst 24.2% were either unsure or disagreed.A recently publishedpilot study hasrevealedthat midwives receive approximately four hours immunisation education in Australian degree courses [43]. This education can be spread across differing unitsandacrossdifferingyearsofanundergraduatecourse.Theresults of our study have demonstrated that this is inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…Education related to vaccines is heterogeneous and diverse. In Spain, this is dependent on the universities, as the design of education programs tend to be flexible, although the final objective is to obtain specific competences that are defined at the state level [ 12 , 14 ]. The management of vaccination interventions is carried out in Spain by Nursing professionals, but collaboratively with the physician, not as an independent intervention, as in other countries such as the UK, where the prescription of pharmacological products by Nurses is recognized and included in the training programs of the different healthcare specialties.…”
Section: Introductionmentioning
confidence: 99%